COMPULSORY METHODS IN TEACHING ESP - Samadova , Marguba; Ziyayeva , Muhayyo (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The current article discusses the main methodology of teaching ESP for adult learners. There are covered some specific approaches and techniques widely used in ESP classroom. Not only vocabulary but also other four language skills such as listening, speaking, reading and writing demand special compulsory methods to teach effectively due to the function and form of language utilized in the specific sphere. That`s because, ESP teaching is considered as the one of the challenging fields of education.